Industrial Biotransformations - Liese, Andreas Seelbach, K (Wiley-VCH, 2000)
"Industrial Biotransformations - a user-friendly and application-oriented up-to-date overview of one-step biotransformations of industrial importance." "The data conferring each process is arranged in a convenient format to survey so that the processes can easily be compared. Each set of data is accompanied by key literature citations. As far as flow sheets of the processes are available, these are given reduced to their significant elements. An extensive index classified by substrates, products, enzymes, and companies provides direct access to each process organized in the order of enzyme classes. The reader will find all significant parameters characterizing the biotransformation itself and the process."--Jacket.